FLOUTING THE MAXIMS OF COOPERATIVE PRINCIPLES: A PRAGMATIC ANALYSIS OF JOE BIDEN’S INAUGURAL SPEECH - OGBOR, Theophilus Sunday (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
Speakers are required to follow certain conversational maxims to successfully relate meanings during conversational exchanges. However, some speakers violate these maxims for different reasons. This study investigates President Joe Biden's 46th inaugural speech to first, identify instances where conversation maxims were flouted and second, determine the dominant maxims that were flouted. Applying insights from Grice’s (1975) conversation maxims, the study employs a qualitative and descriptive approach in examining eight (8) utterances purposively selected from the speech. The findings revealed that the conversation maxims flouted were those of quantity, relation, and manner. The most common flouted maxims were those of quantity and manner. The data contained no instances of flouting the maxim of quality. The study submits that speech writers or presenters do not always follow Grice's conversational maxims, which causes them to be uncooperative in instances where cooperation is required.